ANALISIS BIAYA PEMASARAN MENURUT JENIS PRODUK TERHADAP LABA PADA PERUSAHAAN ROTI MEGA SARI BAKERY KEBUMEN - Kristanti, Ika Neni (P4M STIE Putra Bangsa, 2014)
Marketing costs include all costs incurred since the finished product until the product produced is converted back to cash. Thus marketing costs include the costs of warehousing, advertisement, sale, packaging and packing, credit and billing, accounting and marketing. Therefore, the cost of marketing the company became an important part of the overall costs incurred by the company, because of the importance of marketing costs for the company, the author helps the company to know which products are higher marketing costs and remedy know which product is better in improving the company's net profit according to types of products. Authors conducted a study on company Mega Sari Bakery Kebumen. The company sells ten bakery products with different prices. therefore great to find a great marketing costs and profits of each product cost analysis by type of product marketing at the company Mega Sari Bakery Kebumen, so that the product is known to have the highest marketing costs of ten products are bales while the highest profit on a cream product jumbo cheese because of high levels of sales proceeds.